2013
DOI: 10.1111/cch.12042
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of undetected developmental delays in Iranian children

Abstract: The prevalence of undetected developmental delays in Iranian children screened by the ASQ questionnaires ranged from 3.69% to 4.31% in different developmental domains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
34
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 46 publications
5
34
1
3
Order By: Relevance
“…In our study, the percentage of suspected development delay at the baseline in interventions groups was consistent with a study carried out by Kyerematen et al (16) on the application of the ASQ in child development in a low-income Peruvian shantytown population. Of the 129 children in the study (average age 22 ± 6.8 months), A study in the Islamic Republic of Iran by Sajedi et al (17) using the ASQ showed Iranian children delayed in the communication, gross motor, fine motor, problem-solving and social-personal domains (3.87%, 4.04%, 4.31%, 4.15% and 3.69%, respectively). Alptekin (18) reported that the prevalence of developmental delay by using the ASQtransforming rehabilitation (ASQ-TR) during childhood in Turkey was 6.4% in a community-based sample consisting of children aged 3-60 months.…”
Section: Discussionmentioning
confidence: 95%
“…In our study, the percentage of suspected development delay at the baseline in interventions groups was consistent with a study carried out by Kyerematen et al (16) on the application of the ASQ in child development in a low-income Peruvian shantytown population. Of the 129 children in the study (average age 22 ± 6.8 months), A study in the Islamic Republic of Iran by Sajedi et al (17) using the ASQ showed Iranian children delayed in the communication, gross motor, fine motor, problem-solving and social-personal domains (3.87%, 4.04%, 4.31%, 4.15% and 3.69%, respectively). Alptekin (18) reported that the prevalence of developmental delay by using the ASQtransforming rehabilitation (ASQ-TR) during childhood in Turkey was 6.4% in a community-based sample consisting of children aged 3-60 months.…”
Section: Discussionmentioning
confidence: 95%
“…Prevalence rates in these studies varied between 3 and 5% and the age range was between 4 and 60 months. [6][7][8][9][10] All of these studies used the ASQ, second or third edition, to assess gross motor delay. Our results show that 4.4% of the children were delayed in gross motor skills and results are therefore comparable.…”
Section: Discussionmentioning
confidence: 99%
“…language, cognition, social, fine or gross motor skills), 17,25,26 but no sex differences have been reported before in the area of gross motor skills. [6][7][8]12 A potential explanation could be the presence of sex differences in gross motor skill development in pre-school-aged children. Literature shows boys tend to outperform girls in ball skills, [27][28][29] whereas girls seem to perform better at locomotor skills 28,29 and balance skills.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Little is known about the epidemiology and clinical presentation of ASD in South-East Asia, South America, and Africa (Baxter et al, 2015;de Vries, 2016;Elsabbagh et al, 2012). For children who are developmentally delayed, prevalence rates are likely even higher than reported, since children with milder and more subtle signs are likely to go unnoticed (Sajedi, Vameghi, & Kraskian Mujembari, 2014). Given the increasing developmental burden in LMIC (Lawn et al, 2014), it is essential to identify at-risk and affected children as early as possible.…”
Section: Introductionmentioning
confidence: 99%